Nilai Tukar Petani dan Pola Konsumsi Rumah Tangga (Studi Kasus: Petani Tanaman Pangan dan Hortikultura di Kecamatan Sabak Timur Kabupaten Tanjung Jabung Timur) - Evi Adriani; Hasminidiarty Hasminidiarty; Ali Fahmi (Universitas Batanghari, 2020)
The structure of household expenditure describe the purchasing power of households. For farmer households, their purchasing power is reflected in the exchange rate of the farmers (NTP). NTP describe the higher purchasing power is also higher, which will influence the consumption patterns of farmers.This study aims to: 1) describe the characteristics of farmers, 2) calculate the exchange rate farmers (NTP) and 3) to analyze the pattern of household consumption and horticulture crop farmers in the Eastern District of Muara Sabak. Primary data type with purposive sampling method, were analyzed with descriptive methods in the form of table distibusi frequency and cross tabulation. The results showed: 1) 82.5%farmers belonging to the productive age, the program received by farmers only PAJALELE program, the number of household members mostly 3-4 people and no one including smallholders to own property ownership status of more than 50%. Crops planted by farmers are rice, corn and beans (soy and peanut) and horticultural chili, cucumber, beans, cabbage, eggplant, kale, dragon fruit and litchi. A total of 95% had a second job, the main income of the average farmer Rp. 14,453,162 per growing season or Rp. 3,613,290.5 per month, the average revenue side Rp.2.658.667; 2)NTP did not show a significant difference to household NTP (NTPRP) respectively are 1.47045 and 1.67339 with NTP value distributions for each respondent so lame; 3) The consumption pattern comprising farmers of food and non food consumption in which the average number of non-food consumption is greater than consumption of food. Food consumption is dominated by rice, while non contribute most to the consumption of processed foods. Consumption expenditure for transportation of proportion is highest among the other non-food consumption. Advisable to socialize and educate farmers about the smart and healthy consumption patterns that consumption of great benefit to the quality of human resources and increase agricultural production.